Empowering Community Development Through the Application of Buddhist Principles: A Case Study of Saiyoi Subdistrict, Nernmaprang District, Phitsanulok Province - Suksawas, Wanlapat; Soithong, Parinya (Journal of International Buddhist Studies, 2024)
This research explores the intricate connection between Buddhism and community engagement in the Saiyoi subdistrict, Nernmaprang district, Phitsanulok province. Grounded in compassion, ethical growth, and spiritual values, Buddhism’s ethical framework forms the core of the study. It examines how this framework, combined with communal participation in Buddhist rituals and events, as well as the shared sense of responsibility inspired by Buddhist teachings, fosters community engagement. Using a qualitative research approach, data were collected from 25 local leaders actively involved in community work. These informants, meeting specific criteria, participated in in-depth interviews that provided a profound understanding of their experiences, beliefs, and emotions. The analysis employed a content analysis approach, systematically organizing textual data into concise key findings. The research reveals a compelling narrative of community leadership, proactive development, and the transformative influence of Buddhism. It sheds light on how Buddhism not only promotes community unity but also serves as a catalyst for collective well-being and ethical growth. This study underscores the potential for spiritual and philosophical traditions to drive community engagement, emphasizing the role of cultural and spiritual values in shaping community dynamics. The insights offered valuable lessons for fostering well-being in contexts where Buddhism or similar traditions hold a central place.